Efficiency of hybrid surgical treatment of the aortic arch and descending thoracic aorta aneurysm - V. V. Shlomin; P. B. Bondarenko; E. A. Shloydo; P. D. Puzdriak; Yu. P. Didenko; I. R. Uzhakhov; K. A. Petrova; A. V. Gusinskiy; A. A. Erofeev; K. R. Akimova (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. Assessment of the mid-term results after various types of debranching in hybrid surgery of the aortic arch and descending thoracic aorta.METHODS AND MATERIALS. 47 patients with various pathologies of the aortic arch and descending thoracic aorta were operated on. Six of them suffered from type IIIa dissection and 26 from type IIIb dissection according to DeBakey classification, 15 patients had true aortic aneurysms. The following interventions were performed: total aortic arch debranching (n=5), cross subclavian-subclavian-left-common carotid (n=14) or cross carotid-carotid-subclavian bypass (n=7); subclavian-carotid transposition or bypass (n=12); Chimney technique for the aortic arch aneurysm (n=8); in situ fenestration of the endoprosthesis (n=1). Elective surgery was performed in 32 patients, emergency in 15.RESULTS. Technical success achieved in 100 %. The overall hospital mortality rate was 10.6 % (n=5), elective surgery mortality rate was 9.3 % (n=3), in emergency cases - 13.3 % (n=2). Causes of mortality: stroke (n=1), multiple organ failure after prosthetic ascending aorta due to retrograde dissection after stent graft implantation (n=1), pneumonia (n=1), acute myocardial infarction (n=1), profuse bleeding (n=1). Cumulative survival rate was 87.5 % over 5 years, freedom from reinterventions - 89.1 %. During the first year of observation, 3 patients underwent stent graft replacement of the descending thoracic aorta due to formation of a dissection below the primary stent graft (n=1), open prosthesis of the ascending aorta due to it retrograde dissection (n=1), endofixation of the stent graft with embolization of the false lumen (n=1).CONCLUSION. Hybrid surgery on the aortic arch and the descending thoracic aorta is safe and effective treatment. Regular follow-up and timely treatment of complications in the long term after hybrid or endovascular interventions are necessary to improve long-term results.